A New Flexible and 360° Rotating Shaft Needle-Holder for Microneurosurgery: Technical Note - Menovsky, T.; De Ridder, D. (min - Minimally Invasive Neurosurgery, 2011)
Microsuturing in a narrow and/or a deep operating space is technically challenging and classical microinstruments such as a bayonet microneedle-holder have their limitation, mainly related to their in-built rigidity. In this technical note, a new flexible and 360° rotating shaft microneedle-holder made from nitinol is presented.
Keywords: microneedle-holder; microneurosurgery; key-hole; dura tear; suturing